Modelling and forecasting liquidity supply using semiparametric factor dynamics - Wolfgang Karl Härdle; Nikolaus Hautsch; Andrija Mihoci (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
We model the dynamics of ask and bid curves in a limit order book market using a dynamic semiparametric factor model. The shape of the curves is captured by a factor structure which is estimated nonparametrically. Corresponding factor loadings are assumed to follow multivariate dynamics and are modelled using a vector autoregressive model. Applying the framework to four stocks traded at the Australian Stock Exchange (ASX) in 2002, we show that the suggested model captures the spatial and temporal dependencies of the limit order book. Relating the shape of the curves to variables reflecting the current state of the market, we show that the recent liquidity demand has the strongest impact. In an extensive forecasting analysis we show that the model is successful in forecasting the liquidity supply over various time horizons during a trading day. Moreover, it is shown that the model's forecasting power can be used to improve optimal order execution strategies.
urn:nbn:de:hebis:30-70742
Keywords: C14; C32; C53; G11; 330; Limit Order Book; Liquidity Risk; Semiparametric Model; Factor Structure; Prediction; Wertpapierhandel; Aktienmarkt; Marktliquidität; Prognoseverfahren; Nichtparametrisches Verfahren; Faktorenanalyse; Theorie; Schätzung; Australien